Cadmium and lead concentrations in the dorsal muscles of spotted knifefish (Chitala ornata Gray) from Laguna de Bay, Philippines - Racquel D. Concepcion; John Paul S. Domingo; Hilarie P. Orario; Paolo Ramon D.C. Pacheco; Kenneth Jay Solis; Noel F. Alfonso (Journal of Trace Elements in Medicine and Biology, 2026)

The influence of tree canopy cover data choices on urban ecosystem accounting - Levi T. Sweet-Breu; Gregory S. Cermak; Lucila M. Corro; Peter C. Ibsen; Mehdi P. Heris; Raimundo Atal; Ryan A. McManamay; Jay E. Diffendorfer; Kenneth J. Bagstad (Ecosystem Services, 2026)

Eco-engineered vertical seawall panels with augmented habitat complexity can create a novel and biodiverse ecosystem in a coastal megacity - Thea E. Bradford; Juan Carlos Astudillo; Charlene Lai; Rainbow W.S. Leung; Jay J. Minuti; Rebecca L. Morris; Stephen J. Hawkins; Janet Kit Yan Chan; Cheryl K.C. Chu; Kenneth Mei Yee Leung (Marine Environmental Research, 2026)

Evaluating ecological concrete cubes with recycled oyster shell aggregates for oyster reef restoration - Peng Zhao; Haijie Yang; Hongyou Jiang; Xinran Ji; Yao Xie; Chunsheng Liu; Jay J. Minuti; Thea E. Bradford; Kenneth Mei Yee Leung (Marine Environmental Research, 2026)

Parkinson’s disease impairs grip force release during a sinusoidal force tracking task - Sara Davidson; Kenneth Learman; Anson B. Rosenfeldt; Eric Zimmerman; Jay L. Alberts (Experimental Brain Research, 2026)
The generation, modulation, and release of grip force underlie skilled manual dexterity and object interaction. Advancing age and neurological disease compromise force generation; the impact of age and pathology on the dynamic control of grip force release is unclear. The aim of this project was to determine the impact of age and Parkinson’s disease (PD) on grip force generation and release. Young adults (YA, n = 10, 18–28 years), older adults (OA, n = 10, 57–77 years), and people with PD (PwPD, n = 10, 56–75 years) completed a sinusoidal force tracking task using a precision grip with their dominant hand. Maximum grip force was not different between groups, however, OA relative to YA exhibited deficits in force generation, release and amplitude scaling. Although PwPD had global declines in force control, force release was disproportionately affected compared to force generation. The ability to scale force during its generation and release was compromised by PD. Two-point discrimination of the thumb and index fingers was impaired in PwPD and was moderately correlated with force tracking accuracy and force amplitude. While aging impacts grip force generation and release similarly during a task requiring continuous grip force modulation, PD disproportionately affects grip force release compared to generation. Force amplitude progressively decreases in older adults and PwPD. Potential sources of PD deficits include neural circuitry changes between the prefrontal cortex and striatum, impaired sensorimotor integration, and altered motor unit structure and function. Additional work is focused on identifying the neural mechanism(s) underlying impaired control and regulation of grip forces in PwPD.

Greening of grey and murky harbours: enhancing biodiversity and ecosystem functioning on artificial shorelines - Thea E. Bradford; Juan Carlos Astudillo; Charlene Lai; Rainbow W.S. Leung; Jay J. Minuti; Stephen Hawkins; Rebecca L. Morris; Janet K.Y. Chan; Kenneth Mei Yee Leung (Marine Pollution Bulletin, 2025)

Turning riprap into reefs: Integrating oyster shells into shoreline armouring - Thea E. Bradford; Chi C. Lo; Juan Carlos Astudillo; Rainbow W.S. Leung; Charlene Lai; Jay J. Minuti; Carmen K.M. Wong; Stephen J. Hawkins; Rebecca L. Morris; Kenneth Mei Yee Leung (Marine Pollution Bulletin, 2025)

Modeling Wetland Resources for Spring Migratory Waterbirds Under Different Agricultural Management Scenarios in the Iowa Portion of the Prairie Pothole Region, USA - Mark E. Mitchell; Michael J. Anteau; Aaron T. Pearse; Tammy Newcomer-Johnson; Jay Christensen; William Crumpton; Brian Dyson; Timothy J. Canfield; Matthew Helmers; David Green; Kenneth J. Forshay (Wetlands, 2025)
Constructed water quality wetlands, designed to accept tile drainage and surface runoff, are a promising solution for reducing surface water nutrient loading from agricultural systems. In addition to their water quality benefits, these systems may also offset losses of migratory waterbird stopover sites resulting from historical and future agricultural drainage modernization. To assess this possibility, we developed spatially explicit habitat models informed with expert opinion to explore the: 1) potential of water quality wetlands to provide suitable stopover resources for waterbirds during spring migration; and 2) the extent these wetlands can offset likely losses of stopover resources due to drainage modernization. We focused our modeling on the Iowa portion of the Prairie Pothole Region of North America as it was a historically important area within this vital region for waterbirds, but it has experienced widespread subsurface drainage. Model results indicate that unmitigated drainage modernization is likely to have a large negative effect on spring migratory resources for dabbling ducks and shorebirds and minimal effect on diving ducks. Water quality wetland installations are likely to provide habitat for dabbling and diving ducks, but wetland installation is unlikely to completely offset habitat losses for dabbling ducks and shorebirds. Drainage modernization aside, our results indicate that water quality wetlands can address several environmental issues associated with agricultural expansion and intensification by improving water quality and providing wetland resources for waterbirds and other organisms. Field-scale research is needed to validate these results.

Grip force release is impaired in parkinson’s disease during a force tracking task - Sara Davidson; Kenneth Learman; Eric Zimmerman; Anson B. Rosenfeldt; Jay L. Alberts (Experimental Brain Research, 2025)

Urban tree cover provides consistent mitigation of extreme heat in arid but not humid cities - Peter C. Ibsen; Benjamin R. Crawford; Lucila M. Corro; Kenneth J. Bagstad; Brandon E. McNellis; George D. Jenerette; Jay E. Diffendorfer (Sustainable Cities and Society, 2024)

Older adults are impaired in the release of grip force during a force tracking task - Sara Davidson; Kenneth Learman; Eric Zimmerman; Anson B. Rosenfeldt; Mandy Koop; Jay L. Alberts (Experimental Brain Research, 2024)
Age-related changes in force generation have been implicated in declines in older adult manual dexterity. While force generation is a critical aspect of the successful manipulation of objects, the controlled release of force represents the final component of dexterous activities. The impact of advancing age on the release of grip force has received relatively little investigation despite its importance in dexterity. The primary aim of this project was to determine the effects of age on the control of force release during a precision grip tracking task. Young adults ( N = 10, 18–28 years) and older adults ( N = 10, 57–77 years) completed a ramp-hold-release (0–35% of maximum grip force) force tracking task with their dominant hand. Compared to young adults, older adults were disproportionately less accurate (i.e., less time within target range) and had more error (i.e., greater relative root mean squared error) in the release of force, compared to generation of grip force. There was a significant difference between groups in two-point discrimination of the thumb, which was moderately correlated to force control across all phases of the task. The decline in force release performance associated with advanced age may be a result of sensory deficits and changes in central nervous system circuitry.

A review of ecosystem services from edge-of-field practices in tile-drained agricultural systems in the United States Corn Belt Region - Mark E. Mitchell; Tammy Newcomer-Johnson; Jay Christensen; William Crumpton; Brian Dyson; Timothy J. Canfield; Matthew Helmers; Kenneth J. Forshay (Journal of Environmental Management, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Variants in GCNA, X-linked germ-cell genome integrity gene, identified in men with primary spermatogenic failure - Jimmaline J. Hardy; Margot J. Wyrwoll; William Mcfadden; Agnieszka Malcher; Nadja Rotte; Nijole C. Pollock; Sarah Munyoki; Maria V. Veroli; Brendan J. Houston; Miguel J. Xavier; Laura Kasak; Margus Punab; et al. (Human Genetics, 2021)

Nucleotide P2Y1 receptor agonists are in vitro and in vivo prodrugs of A1/A3 adenosine receptor agonists: implications for roles of P2Y1 and A1/A3 receptors in physiology and pathology - Theodore E. Liston; Sonja Hinz; Christa E. Müller; Deborah M. Holstein; Jay Wendling; Roger J. Melton; Mary Campbell; William S. Korinek; R. Rama Suresh; Dane A. Sethre-Hofstad; Zhan-Guo Gao; Dilip K. Tosh; et al. (Purinergic Signalling, 2020)

High Energy Side and Rear American Football Head Impacts Cause Obvious Performance Decrement on Video - Adam J. Bartsch; Daniel Hedin; Jay Alberts; Edward C. Benzel; Jason Cruickshank; Robert S. Gray; Kenneth Cameron; Megan N. Houston; Tyler Rooks; Gerald McGinty; Erick Kozlowski; Steven Rowson; et al. (Annals of Biomedical Engineering, 2020)

Multidisciplinary Observing in the World Ocean’s Oxygen Minimum Zone Regions: From Climate to Fish — The VOICE Initiative - Véronique Garçon; Johannes Karstensen; Artur Palacz; Maciej Telszewski; Tony Aparco Lara; Denise Breitburg; Francisco Chavez; Paulo Coelho; Marcela Cornejo-D’Ottone; Carmen Santos; Björn Fiedler; Natalya D. Gallo; et al. (Frontiers in Marine Science, 2019)

Ocean Data Product Integration Through Innovation-The Next Level of Data Interoperability - Justin J. H. Buck; Scott J. Bainbridge; Eugene F. Burger; Alexandra C. Kraberg; Matthew Casari; Kenneth S. Casey; Louise Darroch; Joaquin Del Rio; Katja Metfies; Eric Delory; Philipp F. Fischer; Thomas Gardner; et al. (Frontiers in Marine Science, 2019)

Longer exercise duration delays post-exercise recovery of cardiac parasympathetic but not sympathetic indices - Scott Michael; Ollie Jay; Kenneth S. Graham; Glen M. Davis (European Journal of Applied Physiology, 2017)

Submaximal exercise intensity modulates acute post-exercise heart rate variability - Scott Michael; Ollie Jay; Mark Halaki; Kenneth Graham; Glen M. Davis (European Journal of Applied Physiology, 2016)

Importance of mind-muscle connection during progressive resistance training - Joaquin Calatayud; Jonas Vinstrup; Markus Due Jakobsen; Emil Sundstrup; Mikkel Brandt; Kenneth Jay; Juan Carlos Colado; Lars Louis Andersen (European Journal of Applied Physiology, 2016)

Characterization of the microbial community structure and the physicochemical properties of produced water and seawater from the Hibernia oil production platform - C. William Yeung; Kenneth Lee; Susan Cobanli; Tom King; Jay Bugden; Lyle G. Whyte; Charles W. Greer (Environmental Science and Pollution Research, 2015)

Correction - Reid A. Miner; Robert C. Abt; Jim L. Bowyer; Marilyn A. Buford; Robert W. Malmsheimer; Jay O'Laughlin; Elaine E. Oneil; Roger A. Sedjo; Kenneth E. Skog (Journal of Forestry, 2015)

Optimizing conservation strategies for Mexican free-tailed bats: a population viability and ecosystem services approach - Ruscena Wiederholt; Laura López-Hoffman; Colleen Svancara; Gary McCracken; Wayne Thogmartin; Jay E. Diffendorfer; Brady Mattson; Kenneth Bagstad; Paul Cryan; Amy Russell; Darius Semmens; Rodrigo A. Medellín (Biodiversity and Conservation, 2015)

Soil Carbon and Nitrogen Storage in Upper Montane Riparian Meadows - Jay B. Norton; Laura J. Jungst; Urszula Norton; Hayley R. Olsen; Kenneth W. Tate; William R. Horwath (Ecosystems, 2011)

Identification of a Major Xylanase from Aspergillus flavus as a 14-kD Protein - Jay E. Mellon; Peter J. Cotty; Kenneth A. Callicott; Hamed Abbas (Mycopathologia, 2011)

Heme-copper/dioxygen adduct formation relevant to cytochrome c oxidase: spectroscopic characterization of [(6L)FeIII-(O22?)-CuII]+ - Reza A. Ghiladi; Hong-wei Huang; Pierre Monne-Loccoz; Jay Stasser; Ninian J. Blackburn; Amina S. Woods; Robert J. Cotter; Christopher D. Incarvito; Arnold L. Rheingold; Kenneth D. Karlin (JBIC Journal of Biological Inorganic Chemistry, 2005)

Comparing Simulated and Measured Soil Organic Carbon Content of Clay Soils for Time Periods Up to 60 Years - Kenneth N. Potter; Steven R. Potter; Jay D. Atwood; Jimmy R. Williams (Environmental Management, 2004)

Effect of iron limitation on the cadmium to phosphorus ratio of natural phytoplankton assemblages from the Southern Ocean - Jay T. Cullen; Zanna Chase; Kenneth H. Coale; Steve E. Fitzwater; Robert M. Sherrell (Limnology and Oceanography, 2003)
There is considerable interest in the biogeochemical cycling of cadmium (Cd) and phosphate (PO 4 ) in surface waters, driven in part by the ongoing development of a paleonutrient proxy that utilizes Cd preserved in fossil planktonic foraminifera to determine past PO 4 utilization efficiencies in ocean surface waters. The present article reports the results of a field study into the effects of Fe limitation on the Cd : P composition of natural assemblages of marine phytoplankton in the Antarctic Zone of the Pacific sector of the Southern Ocean. Iron enrichment to shipboard incubation bottles led to increases in community growth rate and final biomass. After 10.7 d of incubation, the climax community was dominated by large diatoms of the genus Fragillariopsis, Pseudonitzschia , and Nitzschia . Direct measurements of phytoplankton metal : P ratios from controlled shipboard experiments indicate that Cd : P, Co: P, and Zn : P ratios decreased from control values with increasing initial dissolved Fe concentrations in the incubation bottles, by factors of ~2–10 at highest Fe additions. We suggest that the effect of Fe limitation on resident diatoms is to decrease growth rate, leading to elevated cellular Cd content. The dissolved Cd : P ratio in iron‐limited surface waters of the Southern Ocean may, therefore, respond to the supply of Fe to the resident phytoplankton community, which has implications for the developing paleonutrient proxy. We suggest that the biological uptake of Cd and P is independent of the dissolved Cd: PO 4 ratio. As a consequence, the results argue against the use of empirical Rayleigh fractionation models or models with fixed phytoplankton uptake ratios to account for regional variability in surface water dissolved Cd : PO 4 .

Behaviour: an important diagnostic tool for Lake Malawi cichlids - Jay R Stauffer; Kenneth R McKaye; Ad F Konings (Fish and Fisheries, 2002)
Historically, the cichlid fishes of Lake Malawi, which probably represent one of the best examples of rapid radiation of vertebrates, have been diagnosed with morphological and genetic data. Many of the populations once thought to be conspecific have been hypothesized to be separate species based on behavioural data. The use of behavioural data, as expressed in mate choice based on colour patterns or bower shapes, has been successfully used to diagnose both rock‐dwelling and sand‐dwelling cichlid species. Additionally, a combination of bower shapes and courtship patterns have been used as synapomorphies to diagnose genera within the Lake Malawi cichlid flock. It is concluded that taxonomists need to include behavioural data with morphological and genetic databases to diagnose species and to determine the phylogenetic relationships within this diverse assemblage of fishes.

MOVEMENTS AND POPULATION STRUCTURE OF HUMPBACK WHALES IN THE NORTH PACIFIC - John Calambokidis; Gretchen H. Steiger; Janice M. Straley; Louis M. Herman; Salvatore Cerchio; Dan R. Salden; Urbán R. Jorge; Jeff K. Jacobsen; Olga Von Ziegesar; Kenneth C. Balcomb; Christine M. Gabriele; Marilyn E. Dahlheim; et al. (Marine Mammal Science, 2001)
A bstract Despite the extensive use of photographic identification methods to investigate humpback whales in the North Pacific, few quantitative analyses have been conducted. We report on a comprehensive analysis of interchange in the North Pacific among three wintering regions (Mexico, Hawaii, and Japan) each with two to three subareas, and feeding areas that extended from southern California to the Aleutian Islands. Of the 6,413 identification photographs of humpback whales obtained by 16 independent research groups between 1990 and 1993 and examined for this study, 3,650 photographs were determined to be of suitable quality. A total of 1,241 matches was found by two independent matching teams, identifying 2,712 unique whales in the sample (seen one to five times). Site fidelity was greatest at feeding areas where there was a high rate of resightings in the same area in different years and a low rate of interchange among different areas. Migrations between winter regions and feeding areas did not follow a simple pattern, although highest match rates were found for whales that moved between Hawaii and southeastern Alaska, and between mainland and Baja Mexico and California. Interchange among subareas of the three primary wintering regions was extensive for Hawaii, variable (depending on subareas) for Mexico, and low for Japan and reflected the relative distances among subareas. Interchange among these primary wintering regions was rare. This study provides the first quantitative assessment of the migratory structure of humpback whales in the entire North Pacific basin.

6-hydroxydopamine lesion of rat nigrostriatal dopaminergic neurons differentially affects nicotinic acetylcholine receptor subunit mRNA expression - Kathryn J. Elliott; Jay M. Jones; Aida I. Sacaan; G. Kenneth Lloyd; Janis Corey-Naeve (Journal of Molecular Neuroscience, 1998)